Purrfect Cafe / Aniq Irfan Haqeem Romelan ... [et al.] - Romelan, Aniq Irfan Haqeem; Abdul Halim, Nabilah Syamimi; Mazli, Nurin Zahin; Abdul Latif, Nur Asilah Awatif; Ahmad, Inayatul Nur (2021)
Nowadays, most businesses choose a unique business pattern and can be said to be modern in line over the time. This is because most customers want something different, especially young people who want a beautiful and Instagrammable place to eat or hang out. Therefore, our business took steps to provide a cafe that sells western food and has the uniqueness of providing a place for pets such as cats. Since we have a place for cats, we also provide cat sitting and grooming services. Purrfect Cafe is a business that combines a food cafe and a place for pet sitting and grooming services. This business has a motto that is to provide the best service to ensure our customers are satisfied and make our cafe as the best in town with affordable prices and give the best rating for us. Next, when talking about the interior design as well as the environment of our cafe, we chose to provide a place that can make them feel calm and comfortable like being at home. We provide a clean environment and have fresh air, a cafe that guarantees fun and enjoyable for our target customers such as families, western food lovers, cat lovers and even suitable for students or people who are stressed at work. In ensuring our motto is achieved, we select our employees who are dedicated in carrying out the work. Our employees are from individuals who are experienced and knowledgeable about cats and how to care of them. While for our kitchen employees, we have individuals who are skilled in kitchen management and have skilled and knowledge in western cuisine to produce quality food products that suit the tastes of our customers. Last, but not least, in this assignment as well, we also provide SWOT analysis for two businesses similar to ours. The purpose of this SWOT analysis is to facilitate us in identifying strengths, weaknesses, opportunities and threats in our business based on the two businesses that we analyzed. Next, we also explain about Business Model Canvas. BMC is a simple, concise and easy to understand way for a business to show its concepts and ideas. BMC roughly has nine blocks that can help a business to plan their smooth running. Among them are value proposition, customer segment, customer relationships, channel, key activities, key resources, key partners, cost structure and revenue streams.